2019
DOI: 10.3928/23258160-20191031-15
|View full text |Cite
|
Sign up to set email alerts
|

PPV, Retinectomy, and Silicone Oil Without Scleral Buckle for Recurrent RRD From Proliferative Vitreoretinopathy

Abstract: BACKGROUND AND OBJECTIVE: To analyze the anatomic success rate of pars plana vitrectomy (PPV), retinectomy, and silicone oil (SO) tamponade without scleral buckle (SB) for repair of recurrent rhegmatogenous retinal detachment (RRD) associated with proliferative vitreoretinopathy (PVR). PATIENTS AND METHODS: Retrospective, consecutive, single-surgeon case series of 28 eyes of 28 patients with PVR-associated RRD repaired with PPV, retinectomy, and SO tamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The primary anatomical success rate after one surgery was 83% (43/52 eyes) and is considered comparable to current attachment rates in complex RRD surgery cases [ 28 , 29 ]. However, it increased to 96% (50/52) after the second surgery.…”
Section: Discussionsupporting
confidence: 70%
“…The primary anatomical success rate after one surgery was 83% (43/52 eyes) and is considered comparable to current attachment rates in complex RRD surgery cases [ 28 , 29 ]. However, it increased to 96% (50/52) after the second surgery.…”
Section: Discussionsupporting
confidence: 70%
“…We found that the single-operation complete retinal reattachment rate was 75% (15/20), the complete retinal reattachment rate was 80% (16/20), and the incomplete retinal reattachment rate was 90% (18/20) for re-vitrectomy for Re-RD in post-vitrectomy eyes. Previous studies have reported that the success rate of resurgery for Re-RD is 60%–95.2% [ 5 , 10 , 13 , 19 21 ]. The reasons for the great disparity among previous reports are not only due to differences in population and surgical methods but also because of differences in the definition of anatomical success and follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the great disparity among previous reports are not only due to differences in population and surgical methods but also because of differences in the definition of anatomical success and follow-up time. For example, the reattachment rate of 82.1% reported by Deaner et al [ 10 ] referred to anatomical reattachment under SO with a single operation after 1 year of follow-up. After SO removal, the complete reattachment rate for a single surgery was 57.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SB can provide additional support in inferior detachments and anterior PVR, some studies suggested that effective retinotomy with proper tamponade during vitrectomy may obviate the requirement of concurrent SB, resulting in less surgical time, cost, and morbidity. 32 33 34 …”
Section: Discussionmentioning
confidence: 99%